Marital happiness as the function of spiritual intelligence - Ajawani J.C.2, *Dr. (Mrs.) Alex M.1 and (International Multidisciplinary Research Journal, 2011)
The pursuit of happiness is an important determinant of human behaviour. It becomes even more vital when a couple enters to new life after marriage. This marital happiness has been claimed to be determined by spiritual intelligence levels of both the partners, also along with other factors. Most recently, Diedrich (2007) has defined spiritual intelligence as choosing between the ego and spirit. The authors intended to study role of spiritual intelligence in marital happiness. It has been assumed that couples with higher level of spiritual intelligence will enjoy better marital happiness. On the basis of scores of spiritual intelligence test, the couples were identified as both high, husband high-wife low, wife high-husband low and both low. Thirty subjects were selected incidentally for each of the four groups and happiness test was administered. The findings confirmed the research hypothesis.